Social networking between mobile introns and their host genes - Stoddard, Barry (2010)
Homing endonucleases have long been known as the orchestrators of intron mobility. However, the extent of their influence on the intron and its genetic and cellular environment is still being elucidated. The accompanying paper emphasizes the importance of temporal control of endonuclease expression on splicing, expression of the host gene and cellular metabolism, while it raises questions to guide future inquiry.